(3GdebJVH ef cJGH LegQI GdfSHs - (3TgGH GdOjf CHi YHO Gddg jGbhJ Hf YHO Gddg GdQhei GdMehi GdHZOGOjs; (3GHf GdSGFH GdcdHj , gTGe Hf eMeO CHj GdfUQ Hf GdSGFH Hf HTQ GdcdHj, CHh GdefPQ,J (B204 (3g` s
(3ChdgG (B:s
(3bGd gTGe Hf eMeO GdSGFH s
(3gh HZjQ NWHIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B149s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B481 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B288 s
Keywords: (3GdJGQjNs